Pengaruh Product Involvement dan Word Of Mouth Terhadap Keputusan Pembelian Produk Skincare Scarelett - Sinulingga, Denio Armanda; Tarigan, Eka Dewi Setia; Siregar, M Yamin; Khairunnisak, Khairunnisak (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to determine and analyze the Influence of Product Involvement and Word Of Mouth on Purchasing Decisions for Scincare Scarelett Products. The research method used is associative research, where variables are measured using a Likert scale. Data collection methods are carried out by interview, with a list of questions (questionnaire) and documentation studies. The population in this study were all Consumers of Scincare Scarelett Products in Medan City, totaling 114 people. Sampling using the saturated sampling method or better known as the census. In this study, the population is relatively small, namely 114 people. Data processing using SPSS software version 23, with descriptive analysis and multiple regression analysis hypothesis testing. The results of the study show that: (1) partially the Product Involvement variable influences the Purchasing Decision of Scincare Scarelett Products. (2) partially the Word Of Mouth variable influences the Purchasing Decision of Scincare Scarelett Products. (3) simultaneously there is a positive and significant influence between the Product Involvement and Word Of Mouth variables influencing the Purchasing Decision of Scincare Scarelett Products.